Living Hadis dalam Tradisi Malam Jumat Majelis Darul ’Ulum Pesantren Serambi Mekkah Padang Panjang - Putra, Ario (Islam Transformatif : Journal of Islamic Studies, 2020)
The Friday night tradition carried out by the Darul ‘Ulum forum Serambi Mecca boarding school is a phenomenon of living hadith which is carried out on the basis of the traditions in the hadith. Darul ‘Ulum Assembly is a recitation assembly located in Serambi Mecca boarding school in Padang Panjang, West Sumatra Province. The type of research is field type research, which is about the phenomenon of living hadith. Research on the phenomenon of living hadith is descriptive, qualitative, and inductive. Means a study conducted to get a general picture of the phenomena of living hadith. Then in this study using a social, cultural and religious approach. The study in this research focused on the Darul ‘Ulum forum Pesantren Integrated Serambi Mecca Padang Panjang. In the tradition of the Friday night, the activity is divided into two sessions. The first event is a joint prayer activity that is carried out after magrib prayer until the isya prayer, while the second activity is recitation conducted after the isya prayer until ten o'clock (22:00) WIB. This Friday night activity is held once a week at the boarding school mosque. The purpose of these activities is to foster the love of the students’ in religion and in religious knowledge which is the vision and mission of the in Serambi Meccaboarding school. The results in this study can be concluded that the tradition carried out by the Darul ‘Ulum boarding school Serambi Mecca is a phenomenon of living hadith. Besides that, there is an important meaning of the existence of the Friday night tradition, which is to increase love for religion and increase students' insight into religious knowledge.